Development and application of a core competency evaluation index system for pediatric asthma specialist nurses in China: a mixed-method study - Yi Qin; Xiaoyan Cai; Yelin Ji; Jianing Lu; Caifeng Zhang; Yan Gao; Shujing Yan; Rongshan Chen; Rulin Huang; Lan Ma; Xiao Chun; Fengxia Yan (BMC Nursing)
Abstract Background Specialist nurses’ core competencies are crucial for pediatric asthma management, yet no evaluation system exists for these competencies. Objective To construct a core competency evaluation index system for pediatric asthma specialist nurses. Design A mixed-method study using semi-structured interview, Delphi method and cross-sectional survey. Methods Literature review and semi-structured interviews were performed to developed the initial competencies evaluation index system for pediatric asthma specialist nurses. A two-round Delphi survey was conducted from May 2022 to August 2022, with 21 experts from four provinces in China to rate the importance of each indicator and propose modifications to the evaluation index system. A questionnaire survey with the evaluation indicators was conducted to investigate the level of nurses’ core competency after pediatric asthma specialist training. Results The effective questionnaire recovery rates were 100% and 95% in two rounds of expert consultation, with expert authority coefficients of 0.892 and 0.910, respectively. The core competency evaluation index system for pediatric asthma specialist nurses included 2 definitions, 6 first-level indicators, 16 second-level indicators and 63 third-level indicators. The Kendall’s W coefficients were 0.343 and 0.384 for the first- and second-level indicators in the second round of consultations. Of 80 questionnaires, 69 were valid, wtith Cronbach’s α coefficients of the first-level indicators ranging from 0.896 to 0.968. Conclusion A core competency evaluation index system for pediatric asthma specialist nurses was developed, and demonstrated to be scientific, reliable, and applicable. Statement of implications The core competency index system for pediatric asthma nurses standardizes the assessments, and supports professional development, ultimately enhancing patient outcomes.